Governing sustainability: land use change impact on the palm oil industry in Riau Province, Indonesia - Yuslaini, Nina; Maulidiah, Sri (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
The aim of this research is to determine the social, economic, and ecological impacts of Land Use Change (LUC) of forest areas into Palm Oil industrial areas. The research method used was exploratory qualitative and analyzed using Nvivo 12 Plus. he findings of this study show that there are several challenges in the industrial land use of oil palm in forest areas in Riau, Indonesia, such as land conflicts between communities, government, private sector, forest destruction, and natural disasters. Therefore, we suggest that in order to expedite the removal of oil palm plantations from forest areas and to expedite the issuance of plantation licenses for community, private, and government entities wishing to enter such areas, both the federal government and local governments must adopt policies and impose sanctions. This study serves as a knowledge base to address the social, economic and ecological issues resulting from Land Use Change (LUC) in the province from forest areas to industrial areas producing oil palm. The conclusion of this research is that Land Use Change (LUC) from forest area to palm oil industry area in Riau Province, Indonesia has positive and negative impacts on social, economic, and ecological aspects in Riau Province, Indonesia. The government of the Indonesian province of Riau benefits from this research on land use change (LUC) in the palm oil sector.